Pengaruh Investasi Terhadap Penyerapan Tenaga Kerja Di Kabupaten Pelalawan - Rudi Sofia Sandika; Yusni Maulida; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The successful achievement of the welfare of a nation can be measured by the extent to which a country can solve a variety of problems that are being faced. One of the problems faced by almost all regions in Indonesia is the high unemployment rate. Employment is an important factor in supporting economic development undertaken by developing countries in order to create equitable economic development. The purpose of this study is to analyze the development of investment and employment in Pelalawan of years 2003-2012 and to analize influence of investment on employment in Pelalawan years 2003-2012. This study uses secondary data in the form of time series with the observation period 2003-2012. Data obtained from Badan Pusat Statistik (BPS) and Badan Penanaman dan Investasi Riau Province’s. Data analysis using regression analysis to determine the effect of investment on employment in Pelalawan. Data processing using SPPS program 17.00. The results showed that the investment is not influence significantly on employment in Pelalawan.Keywords: Investment, Man Power